Jason's women - Okimoto, Jean Davies (Boston : Atlantic Monthly Press, 1986)
Awkward and shy, sixteen-year-old Jason finds self-confidence and a new purpose in his lonely life when he answers a job ad and meets and befriends eighty-year-old Bertha Jane Fillmore and the young Vietnamese refugee girl who is staying with her.
Booklist.
Horn Book.
Notable/Best Books (A.L.A.).
4.9
4.9
7-10.
Keywords: Friendship -- Fiction; Old age -- Fiction; Self-confidence -- Fiction; Vietnam War, 1961-1975 -- Refugees -- Fiction; Elderly -- Fiction; Friendship -- Fiction; Self-perception -- Fiction; Vietnam War, 1961-1975 -- Fiction